Sistema de análise de sinal cardíaco para aplicação em telecardiologia - Arrais Júnior, Ernano (2016)
Cardiovascular problems are among the leading causes of mortality in the World. It is estimated that about 15 % of the world population has died due to cardiovascular problems. In Brazil this number represents almost 30 % of deaths, being the men the most affected by cardiovascular disease, with a percentage of approximately 60 % of the victims. Another alarming factor is that Brazil is among the 10 countries with the highest rate of death from cardiovascular disease. Cardiovascular diseases arise from malfunction of the heart and arteries, the most common are infarction, stroke, cardiac arrhythmias and ischemia. Thus, if a good monitoring cardiac activity is necessary in order to prevent possible inconvenience arising from cardiovascular disorders. In recent years, several solutions in the framework of Telecardiology have been discussed to reduce these numbers, in addition to proposing a better monitoring of individuals (patients) and aid to basic health care units located far from major centers. In this work, It is proposed a system will for ECG signal analysis applied to Telecardiology, aiming to validate cardiological clinical data, specifically cardiac arrhythmias (bradycardia, tachycardia and premature ventricular contraction). The mathematical tool used for analyzing ECG signals is Redundant Discrete Wavelet Transform (RDWT), implemented a version for real-time analysis, and the method used for measuring the ECG characteristics is the method based on thresholds. Then, with this ECG signal characterization system it can validate cardiological clinical reports, or rather, it is a tool to support of medical diagnostics validation. The results were satisfactory, the system showed Sensitivity and Positive Predictivity above 99 %. It will be presented also a study about mothers wavelet that are more appropriate in ECG signals processing.